The Sekujam language of West Kalimantan (Indonesia) - Collins, James T.; Herpanus, Herpanus (Wacana, Journal of the Humanities of Indonesia, 2018)
Almost two hundred years ago, O. van Kessel identified a language group based on a characteristic sound change that yielded -ai in the final position of some words (Van Kessel 1850: 166); Hudson (1970) named this group “Ibanic” after the Iban language widely spoken in Sarawak. Of the numerous members of the Ibanic branch of Malayic, perhaps the Sekujam language is the least known. Although Sujarni et al. (2008: 282-285) provided information about the location and traditions of the Sekujam ethnic group, there is very little information about the language. Based on available colonial and contemporary sources, this essay provides a sketch of this ethnic group, numbering perhaps only 3,000 people, split between two administrative units (residencies). Then, a brief overview of the phonology of Sekujam suggests some of its distinctive characteristics. There follows an overview of the sociolinguistic setting of the Sekujam-speaking communities in the Sekadau residency reflecting the status and functions of Sekujam in the language ecology of this multilingual area. Of interest perhaps is the praxis of split dialogic bilingualism documented in some of the area’s villages and the role of Sekujam in traditional rituals of at least one other ethnic group. Much work remains in the face of rapid social, demographic and economic change.